A remineralizing orthodontic etchant that utilizes calcium phosphate ion clusters - Kim, Hyeryeong; Yoo, Kyung-Hyeon; Yoon, Seog-Young; Choi, Youn-Kyung; Kim, Yong-Il (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to investigate whether a phosphoric acid (H3PO4) solution containing calcium phosphate ion clusters (CPICs) could minimize enamel damage during long-term bracket bonding by dissolving the enamel surface and promoting enamel remineralization. The experimental design is as follows. First, three experimental etchants (H3PO4, CPICs-incorporated H3PO4 solution-I, and CPICs-incorporated H3PO4 solution-II) and two bonding resins (conventional orthodontic resin and self-adhesive orthodontic resin) were used in combination to create six groups, respectively. Each of these six groups was then divided into two sub-groups based on the presence or absence of thermocycling (TC). Twenty samples were assigned to each of the 12 groups (independent variables), and thus a total of 240 metal-bracket attached human premolars were used in this experiment. Bracket debonding was performed on each of 20 premolars in 12 groups, and shear bond strength (SBS) and adhesive remnant index (ARI) values were measured as dependent variables. Next, after applying the three experimental etchants (independent variables) to each of the three enamel samples, and the remineralization of the enamel surface was investigated as a dependent variable. The enamel surface was observed using electron scanning and atomic force microscopy. Furthermore, X-ray diffraction, energy dispersive spectroscopy (EDX) spectrum X-ray spectroscopy, and elemental mapping were performed, and the Knoop microhardness scale measured. As a result of the experiment, first, when the bracket was debonded, SBS did not decrease and residual adhesive was hardly observed in the C2A group (before TC), C2A, and C1C groups (after TC) (p < 0.001). Second, the experimental etchant containing CPICs achieved remineralization while demineralizing the enamel. This was verified through SEM/EDX, element mapping, XRD and AFM. Also, the roughness and microhardness of the enamel surface were better in the remineralized surface by the experimental etchant containing CPICs (p < 0.017). The CPICs-incorporated H3PO4 solution reduced ARI while maintaining SBS during bracket debonding, regardless of whether TC was performed or the type of resin. The etchant containing CPICs was also shown to remineralize the enamel and increase its microhardness.